KEPEMILIKAN INSTITUSIONAL DAN MANAJERIAL, UKURAN DEWAN, DAN UKURAN PERUSAHAAN: ANALISIS PENGARUHNYA TERHADAP KINERJA MELALUI STRUKTUR MODAL - Lay, Sevvie Prissy; Yandi Suprapto; Candy (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the influence of institutional ownership, managerial ownership, board size, and firm size on firm performance, with capital structure serving as the mediating variable. The research focuses on banking companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study employs a quantitative method with a causal–explanatory approach. Secondary data were obtained from annual reports of 47 banking firms that met purposive sampling criteria. Data analysis was conducted using multiple regression and mediation testing through the Structural Equation Modeling (SEM) approach. The results reveal that institutional ownership, managerial ownership, and board size have a significant positive effect on firm performance. Capital structure is found to mediate the relationship between these variables and performance, although excessive debt negatively affects Return on Assets (ROA). In addition, firm size positively contributes to enhancing performance. These findings provide practical implications for managers and regulators in formulating governance strategies and optimal capital structures to strengthen firm performance.